Persepsi Masyarakat Dan Pengunjung Terhadap Ruang Terbuka Hijau (Rth) Imam Bonjol Padang - Marganof Marganof; Teguh Haria Aditia Putra; Fauzan Fauzan (Menara Ilmu : Jurnal Penelitian dan Kajian Ilmiah, 2026)
This study aims to examine the perceptions of the community and visitors regarding the existence of urban green open spaces (GOS) and the management of urban areas, particularly due to their significant role in improving and enhancing environmental quality. In addition, this study seeks to identify public and visitor perceptions of the importance of green open spaces within urban environments.Urban areas serve as residential centers as well as hubs for government services, social services, and economic activities. However, these activities often generate environmental problems such as noise, air pollution, and other forms of environmental degradation. Therefore, green open spaces play a crucial role in mitigating these issues by reducing noise, absorbing carbon dioxide, and producing fresh air, thereby contributing to a healthier urban environment.This research employed a quantitative descriptive method to describe, explain, and summarize various research conditions, situations, phenomena, and variables as they naturally occur. Data were collected through observations, documentation, interviews, and questionnaires administered to community members and visitors as the research respondents.The study focused on the perceptions of the community and visitors regarding the existence of the Imam Bonjol Green Open Space in Padang. Based on one month of research and data analysis using the applicable calculation formula, the assessment covered five sub-variables: aesthetic function, ecological function, health function, social function, and participation. The results showed that the average score across these sub-variables was 78.15%, which falls into the good category. Therefore, it can be concluded that the perceptions of the community and visitors regarding the existence of the Imam Bonjol Green Open Space in Padang are generally positive. Keywords: perception, urban area, observation, green open space, quantitative descriptive.